The red hot chilli cookbook : fabulously fiery recipes for chilli fans - May, Dan (Ryland Peters & Small, 2012)
Trees Can't Dance began over 4 years ago at the world's most northerly chile farm. Against all conventional horticultural wisdom Dan May began growing chiles in the wilds of Northumberland, northern England. It wasn't long before Dan had to find something to do with all the produce. Disappointed with the quality of the chili sauce brands available in the UK, he hit on the idea of filling a gap in the market by producing his own sauces using homegrown ingredients. In this fabulous book, chile guru Dan shares more than 70 recipes celebrating chiles in all their varieties and strengths. Acquaint yourself first with the history of chiles, how to grow them at home, how to identify the key varieties and what gives them their distinctive heat. There are ideas here for every kind of dish: Soups & Salads; Nibbles & Sharing Plates; Entrées; Side Dishes; Sauces, Salsas & Marinades; Sweet Things & Drinks. Mouthwatering recipes include Thai Beef Noodle Soup; Moroccan Spiced Lamb Burgers; Texas Marinated Steak with Stuffed Mushrooms; Sweet Chile-glazed Ham; Quick Chile Lime Mayonnaise; three fiery pasta sauces; Chile Pecan Brownies; and Chile Hot Chocolate.